A prospecção de um oikos roabastiano : ecocrítica, metaliteratura e dualidade em pauta - Morosino, Juliana Terra (2021)
This study aims to investigate the ecological environmental references linked to historical-social and identity issues from the metaliterary exercise present in the Paraguayan literature of Augusto Roa Bastos, more specifically, in his penultimate novel Contravida (1994). Throughout the thesis, we seek, among other themes, to verify the existence of an ecological wisdom evidenced in the voice of the narrator-protagonist and brought to light through the constant rewriting of the self throughout the narrative; as well as the role of the environment in the novel from an Ecocritical perspective, in order to dialogue with the historical-cultural elements that constitute a Paraguayan identity permeated by singularities such as indigenism and bilingualism. We asked ourselves about the possibility of the narrative awakening an ecological awareness and how it manifests itself in the novel. The study is based mostly on Literary Ecocritique, with Greg Garrard, Terry Gifford, Cheryll Glotfelty, Flys Junquera, among others. In addition to Ecocritical analysis, this study is also based, albeit to a lesser extent, on Theories of Literary Space, Cultural Studies, Ecosophy, Critical Theories of Society, as well as on literary criticism, more especially, Latino- American. It concludes that Contravida when read through the lens of Ecocritique and the existing cultural, linguistic and transtextual singularities, provides an opportunity for a sparking of ecocentric consciousness in contrast to the ethnocentric logic so deeply rooted in contemporary man. In this way, Roa Bastos' narrative reverberates the need for a new posture, an environmental praxis enlivened through the trajectory of the narrator-protagonist, highlighting a resignified oikos that stands out in the permanent interdependence between the human and the non-human.